Performance evaluation of a compression algorithm for wireless sensor networks in monitoring applications - Ivanovitch M. D. Silva (2008)
Wireless sensor network (WSN) is an emerging technology that targets multiple applications in the different environments. Its infrastructure is composed of a large number of sensor nodes with a limited physical capacity and low cost. The energy consumption must be as optimized as possible in order to extend its lifetime. The use of data compression techniques can be an advantage in the WSN context, once these techniques eliminate transmission of redundant information and consequently can be adopted to minimize the consumption of energy in the sensor nodes. WSN for monitoring applications can benefit from this technique as it may maximize the lifetime of batteries. The main motivation of this paper is to investigate the performance of a data compression algorithm for WSN in the context of monitoring applications. To validate the proposal, simulation experiments have been performed using the Network Simulator (NS-2) tool.